Carboxymethyl Chitosan as A Homemade Sausage Preservative - Mardiyah Kurniasih; Purwati Purwati; Ratna Stia Dewi; Dadan Hermawan; Eva Vaulina (The Journal of Pure and Applied Chemistry Research, 2019)
Carboxymethyl chitosan has antimicrobial activity. The solubility of carboxymethyl chitosan makes it easy to apply as a food preservative. Sausage is a processed product of meat, and it is classifiedas perishable food. The purpose of this study was to synthesize carboxymethyl chitosan, investigate the microbiological quality and shelf-life of homemade sausage treated with carboxymethyl chitosan. Carboxymethyl chitosan was obtainedthrough the process of carboxymethylation of alkaline chitosan with monochloroacetic acid. Chitosan in the study was synthesizedfrom shrimp skin. Sausages treated with carboxymethyl chitosan then measured water content, ash content, TPC (Total Plate Count) and organoleptic values for four consecutive days. The results showed that carboxymethyl chitosan couldextend the shelf life of sausages both stored at room temperature or cold temperatures.